Efficiency of Bone Marrow-Derived Mesenchymal Stem Cells and Hesperetin in the Treatment of Streptozotocin-Induced Type 1 Diabetes in Wistar Rats - Osama M. Ahmed; Ablaa S. Saleh; Eman A. Ahmed; Mohammed M. Ghoneim; Hasnaa Ali Ebrahim; Mohamed A. Abdelgawad; Mohammed Abdel-Gabbar (MDPI AG, 2023)
Type 1 diabetes mellitus (T1DM) was established to be ameliorated by islet transplantation, but the shortage of the transplanted human islet tissue and the use of immunosuppressive drugs to inhibit the rejection of allogeneic grafts make this type of therapy is limited. Nowadays, therapy with stem cells is one of the most promising future treatments. This kind of therapy could have a profound impact on both replacement, as well as regenerative therapies, to improve or even cure various disorders, including diabetes mellitus. Flavonoids have also been shown to possess anti-diabetic effects. Thus, this study aims to evaluate the effectiveness of the bone marrow-derived mesenchymal stem cells (BM-MSCs) and hesperetin in the treatment of a T1DM rat model. T1DM was induced in male Wistar rats that had been starved for 16 h via intraperitoneal injection of STZ at a dose of 40 mg/kg body weight (b.wt.). After 10 days of STZ injection, the diabetic rats were allocated into four groups. The first diabetic animal group was considered a diabetic control, while the other three diabetic animal groups were treated for six weeks, respectively, with hesperetin (given orally at a dose of 20 mg/kg b.wt.), BM-MSCs (injected intravenously at a dose of 1 × 106 cells/rat/week), and their combination (hesperetin and BM-MSCs). The use of hesperetin and BM-MSCs in the treatment of STZ-induced diabetic animals significantly improved the glycemic state, serum fructosamine, insulin and C-peptide levels, liver glycogen content, glycogen phosphorylase, glucose-6-phosphatase activities, hepatic oxidative stress, and mRNA expressions of NF-κB, IL-1β, IL-10, P53, and Bcl-2 in pancreatic tissue. The study suggested the therapy with both hesperetin and BM-MSCs produced marked antihyperglycemic effects, which may be mediated via their potencies to ameliorate pancreatic islet architecture and insulin secretory response, as well as to decrease hepatic glucose output in diabetic animals. The improvement effects of hesperetin and BM-MSCs on the pancreatic islets of diabetic rats may be mediated via their antioxidant, anti-inflammatory, and antiapoptotic actions.